Biogeochemical properties of sinking particles in the southwestern part of the East Sea (Japan Sea) - Minkyoung Kim; Jeomshik Hwang; TaeKeun Rho; Tongsup Lee; Dong-Jin Kang; Kyung-Il Chang; Suyun Noh; HuiTae Joo; Jung Hyun Kwak; Chang-Keun Kang; Kyung-Ryul Kim (Journal of Marine Systems, 2017)
Abstract This study investigates the biological pump system in the East Sea (Japan Sea) by conducting an analysis of the total particle flux, biogenic material composition, and carbon isotope ratios of sinking particles. The samples were collected for one year starting from March 2011 using time-series sediment traps deployed at depths of 1040 m and 2280 m on bottom-tethered mooring at Station \{EC1\} (37.33°N, 131.45°E; 2300 m water depth) in the Ulleung Basin (UB), southwestern part of the East Sea. The temporal variation in the particulate organic carbon (POC) flux at 1000 m shows a good relationship with the primary production in the corresponding surface water. The ratio of \{POC\} flux at 1000 m to satellite-based primary production in the corresponding region in the \{UB\} was   3%, which is comparable to the values of 2 to 5% estimated from previous studies of other part of the East Sea. The lithogenic material accounted for > 17% of the sinking particles at 1000 m and for a larger fraction of 40 to 60% at 2280 m. The radiocarbon contents of the sinking \{POC\} at both trap depths imply the additional supply of aged POC, with a much greater contribution at 2280 m. Overall, the particle flux in the deep interior of the East Sea appears to be controlled by the supply of complex sources, including aeolian input, the lateral supply of resuspended sediments, and biological production in the surface water.
Keywords: East Sea (Japan Sea)

Sedimentation of particulate organic carbon on the Amundsen Shelf, Antarctica - Minkyoung Kim; Jeomshik Hwang; Sang H. Lee; Hyung J. Kim; Dongseon Kim; Eun J. Yang; SangHoon Lee (Deep Sea Research Part II: Topical Studies in Oceanography, 2016)
Abstract We examined the recent history of sedimentary organic carbon (SOC) accumulation on the western Amundsen Shelf, to help characterize the biological carbon pump in the Amundsen Sea, Antarctica. Vertical sedimentary profiles (in the upper 21-cm) of \{SOC\} content, radio- and stable-carbon isotopes were obtained at four locations in the western Amundsen Sea: near the shelf break, inside the polynya near the Dotson Ice Shelf, and at both the periphery and the center of the Amundsen Sea polynya. Profiles were representative not only of various distances from the coast, but also of various summertime sea ice conditions and bottom depths. The \{SOC\} content (up to 1.1%) and the radiocarbon content were distinctly higher at the periphery and at the center of the polynya than at the other sites. The \{SOC\} and 14C contents were generally consistent with the spatial distribution of primary productivity in the surface water. A linear \{SOC\} accumulation rate of about 1.0 g C m−2 yr−1 was determined from the conventional 14C ages of bulk \{SOC\} below the surface mixed layer at the periphery and at the center of the polynya, for the time period of 3.1–4.7 kyr before present (BP). This linear \{SOC\} accumulation rate was about 20 times greater than the rates determined at the two other sites for the period of 4.6–15.7 kyr BP. Note that all values are for uncorrected 14C ages. At the center of the polynya, a sudden change in \{SOC\} accumulation rate was observed at about 16 cm depth, corresponding to 4.7 kyr BP, implying that changes (during this time period) in physical environments greatly affected primary production, \{SOC\} burial and/or supply of allochthonous particles to this site. The vertical distribution of 14C content in the sediments implies that aged organic matter, likely associated with resuspended sediments, was also being deposited inside the polynya, in addition to autochthonous biogenic particles. If our estimation of \{SOC\} accumulation is extrapolated to the western Amundsen Shelf between 110°W and 120°W, approximately 3×1010 g C yr−1 is buried on the shelf, with  90% of \{SOC\} accumulation occurring in the Amundsen Sea polynya.
International efforts to understanding of the changing Antarctic climate: The \{KOPRI\} expedition to the Amundsen Sea
Keywords: Global carbon cycling